EFEKTIVITAS PUPUK BOKASHI DAN PHOSPAT TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN MENTIMUN (Cucumis sativus L.) VARIETAS ZATAVI F1 - Choirudin Firmansyah; Titik Irawati (Jurnal Ilmiah Hijau Cendekia, 2023)
Thisstudyaimsto:1)Todetermine the interaction on thedosetreatment of bokashi and phospatefertilizersonthegrowthandproduction of cucumberplants(CucumissativusL.)varietyZataviF1.2)determine the effect of treatment on the doseofbokasifertilizeronthegrowthandproduction of cucumberplants(CucumissativusL.)varietyZatafiF1.3)determine the effect of treatment on thedose of phospateonthegrowthandproduction of cucumberplants(CucumissativusL.)varietyZatafiF1.3)determine the effect of treatment on thedose of phospatefertilizeronthegrowthofcucumberplantproduction(CucumissativusL.)varietyZatafiF1.Thisstudyused a FactorialGroupRandomizedDesign(RAK)withtwofactors.Thefirst factor is the doseoforganic fertilizer (bokashi) with 3 levels: 1.3 kg/plot, 1.9 kg/plot, 2.5kg/plot and the secondfactoristheapplicationofHSPAstivaPhospatefertilizer with 3 levels: 20 gr/plant, 25 gr/plant,30gr/plantrepeated3timeswith27treatment plots.Theresultsshowedthat1).Thereisaverynoticeableinteractioninthegenerativephase of thevariableobservationoffruitlength.Therewasarealinteraction of vegetative phase observation variables of plant length and generativephaseobservationvariables of number of fruits/plants and fruit/plantweight on dosing of bokashi and phospatefertilizersonthegrowthandproductionofcucumberplants(CucumissativusL)varietyZataviF1.2) Therewasaverynoticeableeffectofdosingbokasifertilizerin the generativephase of the variableobservation of fruit/plantlengthonthegrowthandproductionofcucumberplants(CucumissativusL) varietyZataviF1.3) Thereisnoeffectofdosingphospatefertilizerin the vegetative and generativephasesonthegrowthandproductionofcucumbers(CucumissativusL)varietiesZataviF1.